2018
DOI: 10.1080/17425255.2018.1550484
|View full text |Cite
|
Sign up to set email alerts
|

How can we best monitor 5-FU administration to maximize benefit to risk ratio?

Abstract: Introduction: 5-FU is currently used as a chemotherapy in several cancers such as head-andneck (H&N) and colorectal cancers (CRC). 5-FU dosing is traditionally based on bodysurface-area, but this strategy is usually associated with severe toxicities. 5-FU is mainly catabolized by dihydropyrimidine dehydrogenase (DPD), and 5-FU dosage adaptation according to DPD status at the first cycle of treatment is now recommended. To further optimize 5-FU-based chemotherapy, a body of evidences justifies therapeutic drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Hence, it is crucial to enhance the sensitivity of chemotherapy drugs. 5‐Fu and DOX are commonly used clinical anti‐tumor chemotherapy drugs, which have inhibitory effects on a variety of human tumors, mainly by inducing tumor cell apoptosis 40–46 . The present study showed that Dem can enhance the chemotherapy sensitivity of pancreatic cancer cells to gemcitabine and colorectal cancer cells to 5‐Fu 10,11 .…”
Section: Discussionsupporting
confidence: 51%
“…Hence, it is crucial to enhance the sensitivity of chemotherapy drugs. 5‐Fu and DOX are commonly used clinical anti‐tumor chemotherapy drugs, which have inhibitory effects on a variety of human tumors, mainly by inducing tumor cell apoptosis 40–46 . The present study showed that Dem can enhance the chemotherapy sensitivity of pancreatic cancer cells to gemcitabine and colorectal cancer cells to 5‐Fu 10,11 .…”
Section: Discussionsupporting
confidence: 51%
“…It is indispensable for many chemotherapy regimens in gastric cancer and intestinal cancer ( 24 ). However, the half-life of fluorouracil is short, and continuous intravenous injection or oral administration may be required for systemic chemotherapy based on fluorouracil ( 25 , 26 ). In the present study, intraperitoneal fluorouracil implants, where fluorouracil was encapsulated within the microcapsules, were used.…”
Section: Discussionmentioning
confidence: 99%
“…Even if 5‐FU remains the reference molecule used in combination with other chemotherapeutic drugs, it is highly toxic and can lead to patients' death 42 . This observation recently suggested a fine monitoring 43 implying assays of dihydropyrimidine dehydrogenase (DPD) activity, 44,45 the enzyme responsible for the catabolism of 5‐FU. Moreover, resistance to 5‐FU is a major clinical problem and its mechanism is highly complex 7 .…”
Section: Discussionmentioning
confidence: 99%